The Evolution of Genetics: Alzheimer's and Parkinson's Diseases - Singleton, Andrew; Hardy, John (Neuron (Cambridge, Mass.), 2016)
Genetic discoveries underlie the majority of the current thinking in neurodegenerative disease. This work has been driven by the significant gains made in identifying causal mutations; however, the translation of genetic causes of disease into pathobiological understanding remains a challenge. The application of a second generation of genetics methods allows the dissection of moderate and mild genetic risk factors for disease. This requires new thinking in two key areas: what constitutes proof of pathogenicity, and how do we translate these findings to biological understanding. Here we describe the progress and ongoing evolution in genetics. We describe a view that rejects the tradition that genetic proof has to be absolute before functional characterization and centers on a multi-dimensional approach integrating genetics, reference data, and functional work. We also argue that these challenges cannot be efficiently met by traditional hypothesis-driven methods but that high content system-wide efforts are required.